Difference of two squares problem
49t² - 9
49t² - 21t + 21t - 9
7t(7t - 3) + 3(7t - 3)
(7t + 3)(7t - 3)
- - - - - - - -
Roots
7t + 3 = 0
7t + 3 - 3 = 0 - 3
7t = - 3
7t/7 = - 3 / 7
t = - 3 / 7
- - - - - - - -
7t - 3 = 0
7t - 3 + 3 = 0 + 3
7t = 3
7t / 7 = 3 / 7
t = 3 / 7
- - - - - - - - - - -
Method 2
49t² - 9 = 0
49t² - 9 + 9 = 0 + 9
49t² = 9
49t² / 49 = 9 / 49
t² = √9 / 49
t = ± 3 / 7
- - - - - - - - -s-
2007-01-14 21:00:29
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
49t^2-9=0
+9 +9
49t^2=9
divide both sides by 49
t^2=9/49
take the square root of both sides
t=+/- square root of 9/49
2007-01-15 01:20:33
·
answer #2
·
answered by zig 1
·
0⤊
0⤋
add 9 to each side 49t^2=9
divide each side by 49 t^2=9/49
Square root each side t=3/7 or -3/7
you can take both the root of the numeater and denominator to get a simplified answer
2007-01-15 01:17:02
·
answer #3
·
answered by jcj7373 2
·
1⤊
0⤋
49t^2 = 9
t^2 = 9 / 49
t = sqrt (9 / 49)
t = + ( 3/7 ) or - ( 3/7 )
2007-01-15 04:47:05
·
answer #4
·
answered by sg 2
·
0⤊
0⤋
49t^2 = 9
t^2 = 9/49
t = Sqrt(9/49) - need to take square root of both sides
t = 3/7 and -3/7
2007-01-15 01:18:28
·
answer #5
·
answered by mkpluslc 1
·
1⤊
0⤋
difference of two squares formula
(a+b)(a-b)=a^2 - b^2
(7t + 3)(7t - 3) = 49t^2 - 9
7t + 3 =0
7t = -3
t = -(3/7)
or
7t - 3 =0
7t =3
t = 3/7
zero property ( if the product is zero one of the factors has to be zero, so one or the other above is true)
2007-01-15 01:21:14
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
factor it
(7t+3)(7t-3)=0
then solve
7t+3=0 7t-3=0
7t=-3 7t=3
t=-3/7 t=3/7
2007-01-15 01:28:44
·
answer #7
·
answered by tini 2
·
0⤊
0⤋
49t^2-9=0
(7t-3)(7t+3)=0
7t-3=0
7t=3
t=3/7
7t+3=0
7t=-3
t=-3/7
2007-01-15 01:16:09
·
answer #8
·
answered by yupchagee 7
·
1⤊
0⤋